2020
DOI: 10.1093/infdis/jiaa494
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Moderate or High-Intensity Combined Exercise on Systemic Inflammation Among Older Persons With and Without HIV

Abstract: Background We investigated whether higher intensity exercise provided greater overall decrease in key markers of inflammation, and whether responses to exercise intensity differed by HIV serostatus. Methods People with HIV (PWH; n=32) and controls (n=37) aged 50-75 completed 12 weeks of moderate-intensity combined exercise then were randomized to moderate- or high-intensity exercise for 12 additional weeks (n=27 and 29, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
1
13
1
Order By: Relevance
“…44,45 Furthermore, a study looking at the effects of exercise suggests that PWH are unable to increase IL-10 expression when compared to HIV-negative individuals. 46 In this study, the relationship between the T cell-monocyte complexes and IL-10 and the interaction between hemoglobin A1C and IL-10 reinforces the notion that complexes arise in the setting of inflammation. 47 Taken together, a state of systemic inflammation in PWH, compounded with diabetes and a lack of adequate inhibitory responses, could enhance the presence of the T cellmonocyte immune complexes.…”
Section: Discussionsupporting
confidence: 81%
“…44,45 Furthermore, a study looking at the effects of exercise suggests that PWH are unable to increase IL-10 expression when compared to HIV-negative individuals. 46 In this study, the relationship between the T cell-monocyte complexes and IL-10 and the interaction between hemoglobin A1C and IL-10 reinforces the notion that complexes arise in the setting of inflammation. 47 Taken together, a state of systemic inflammation in PWH, compounded with diabetes and a lack of adequate inhibitory responses, could enhance the presence of the T cellmonocyte immune complexes.…”
Section: Discussionsupporting
confidence: 81%
“…Beyond the obvious benefits of increasing muscle mass, cardiovascular endurance, and strength, there have been mixed effects on inflammatory biomarkers. [143][144][145] Although some data are available, 93 further studies are needed to evaluate mitochondrial function and ageing in people with HIV in different contexts (eg, with interventions such as calorie restriction, stress reduction, and exercise). Approaches modifying the diet and microbiome that involve probiotics might lower concentrations of D-dimer but did not affect the microbiome.…”
Section: Overall Limitationsmentioning
confidence: 99%
“…Research into the efficacy of an exercise intervention in improving physical and brain health in people living with HIV is less established. Longitudinal intervention studies have primarily focused on physical health outcomes, with evidence of improved blood pressures (BPs), cardiorespiratory fitness (VO 2 max ), inflammatory markers, physical strength, and body composition in people living with HIV following completion of an EXS training program or other activity programs, such as yoga [20][21][22][23][24][25]. The relationship between exercise and cognitive outcomes in people living with HIV has primarily been assessed using association studies and self-reported levels of physical activity.…”
Section: Overviewmentioning
confidence: 99%